Law Enforcement Agencies in the System for the Rights of Entrepreneurs Protection - RAKHMETOLLOV, Askar K.; BEKISHEVA, Sabigul; KIZDARBEKOVA, Antonina S.; AKHMETOVA, Nailya S.; MYRZALIYEVA, Zhanarai T. (Journal of Advanced Research in Law and Economics, 2019)
The urgency of the problem stated in the article is due to the fact that the development of entrepreneurial initiative of citizens directly depends on a number of factors, including protection from illegal acts, actions (inactions) of officials, government bodies and organizations. Therefore, the main purpose of the article is to develop the theoretical foundations of a uniform approach to the formation of a model for organizing the activities of law enforcement agencies to ensure the protection of the rights of entrepreneurs. The leading method for the study of this problem is the method of analysis, which contributed to the consideration of this problem from the inside, by isolating and studying certain parts of law enforcement agencies as an independent form of ensuring the protection of the rights of entrepreneurs. It was also used comparative legal and regulatory methods. The level of trust of entrepreneurs is a direct reflection of the interaction of law enforcement agencies, state bodies and organizations in the field of ensuring the protection of the rights of entrepreneurs, which depends on various aspects, including: legislative support, professionalism of officials, law enforcement practice. The results of the study can be used in modern conditions as a basis for improving the practice of law enforcement in ensuring the protection of the rights of entrepreneurs, in the educational process, as well as in conducting further research on the analyzed field.